2016
DOI: 10.1590/1414-431x20165300
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of early treatment discontinuation and severe anemia in a Brazilian cohort of hepatitis C patients treated with first-generation protease inhibitors

Abstract: The aim of this study was to determine risk factors for adverse events (AE)-related treatment discontinuation and severe anemia among patients with chronic hepatitis C virus (HCV) genotype 1 infection, treated with first-generation protease inhibitor (PI)-based therapy. We included all patients who initiated treatment with PI-based therapy at a Brazilian university hospital between November 2013 and December 2014. We prospectively collected data from medical records using standardized questionnaires and used E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
1
10
0
2
Order By: Relevance
“…SVR was high (98.1%), with no significant differences between groups, in agreement with other Brazilian studies that found an SVR of 91.6‐95% . International studies also showed high rates of response to treatment, ranging from 78.6‐90%, depending on the treatment regimen used …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…SVR was high (98.1%), with no significant differences between groups, in agreement with other Brazilian studies that found an SVR of 91.6‐95% . International studies also showed high rates of response to treatment, ranging from 78.6‐90%, depending on the treatment regimen used …”
Section: Discussionsupporting
confidence: 89%
“…[24][25][26][27] SVR was high (98.1%), with no significant differences between groups, in agreement with other Brazilian studies that found an SVR of 91.6-95%. 13,28,29 International studies also showed high rates of response to treatment, ranging from 78.6-90%, depending on the treatment regimen used. 14,22,[30][31][32] The most recent Brazilian protocol recommends use of ribavirin for patients with cirrhosis, with a lower chance of SVR (genotype 3, men, aged >40 years), or by medical decision, with consideration of previous intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating our results, a Brazilian cohort study developed with 203 patients showed high rates (19.2%) of therapy discontinuation owing to AEs. These authors reported that 41% and 37.5% of the BOC or TVR discontinuations, respectively, also occurred due to hematologic events and cutaneous reactions 20 . It was previously described that patients with comorbidities and advanced cirrhosis are more vulnerable to AEs 18 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Insofar as IFNL3 (IL28B) influences the responsiveness to PEG‐IFN and RBV, polymorphisms in ITPA gene—the most studied gene in our data mining—influence anaemia induced by RBV and strongly correlated to RBV‐induced haemolytic anaemia (RIHA) . The development of RIHA during anti‐HCV treatment is responsible for treatment discontinuation, dose reduction, and consequently decreased SVR. As such, ITPA represents an indirect but important predictor of effective RBV‐based treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…45 This involves activation of Jak-STAT pathway, the third pathway in our analysis, which in turn stimulates the expression of a myriad of ISG, 48 Insofar as IFNL3 (IL28B) influences the responsiveness to PEG-IFN and RBV, [49][50][51] polymorphisms in ITPA gene-the most studied gene in our data mining-influence anaemia induced by RBV 52 and strongly correlated to RBV-induced haemolytic anaemia (RIHA). 53 The development of RIHA during anti-HCV treatment is responsible for treatment discontinuation, 54 pegylated IFN-α/RBV and DAA was shown to be effective in managing viral resistance and relapse following treatment. 57 The interferon signalling pathway constitutes the first-line defence against viral infections.…”
Section: Treatment Type Analysis With the Genes Associated With Hcvmentioning
confidence: 99%